Reconfiguring the eco-system for sustainable healthcare - Mohrman, Susan Albers; Shani, Abraham B. (Emerald, 2014)
Volume 4 extends the examination of Organizing for sustainable healthcare (Volume 2 of the same series, 2012). It presents case studies and theoretical analyses that illustrate practical approaches to, and further the theoretical understanding of, the creation of a more sustainable healthcare. Given economic, ecological, and population trends, the sustainability of healthcare delivery as it is organized today cannot be taken for granted. Politicians, healthcare regulators and professionals worldwide are debating how to redesign todays delivery paradigms to deliver greater value to our societies while consuming fewer resources. Even in countries with national health systems, healthcare organization has been fragmented, diminishing outcome effectiveness and wasting society's resources. With complex value chains and dynamic interactions among various players, the reconfiguration of the healthcare system will require the reconciliation of different often conflicting goals, values, conceptions of social justice, work processes, knowledge bases, and business models. The chapters in this volume build on multiple disciplines and varied approaches to address this complexity.
Keywords: Public health.; Medical policy -- Environmental aspects.; Medical care -- Environmental aspects.; elektronické knihy; electronic books